(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The Seismic design of buildings, the shear walls effect as primary earthquake-resisting elements in The Buildings Multy Story. Structural walls serve as an effective bracing system and have a high capacity for resistance to lateral loads.